2015
DOI: 10.1016/j.ecl.2015.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Body Composition and Bioenergetics by Estrogens

Abstract: SYNOPSIS Evidence from basic, preclinical, and clinical research points to an important role of estradiol (E2) in the regulation of body composition and bioenergetics. There is consistent evidence from basic and preclinical research that the disruption of E2 signaling, through either genetic manipulation (e.g., estrogen receptor deletion) or surgical intervention (e.g., ovariectomy), accelerates fat accumulation, with a disproportionate increase in abdominal fat. Clinical evidence for the regulation of body co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
68
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(76 citation statements)
references
References 72 publications
6
68
0
2
Order By: Relevance
“…This clinical phenotype has often been documented in rodents post-ovariectomy, as well as in chronic hypoestrogenemic models, such as in female Erα −/− , aromatase −/− and Fshr −/− mice 4, 1618 , although in our hands, female Fshr −/− mice are not obese. While in female mice, genetic Fshr deficiency does not seem to protect against the pro-adiposity effects of severe chronic hypoestrogenemia, we questioned whether acute suppression of Fsh by an Fsh Ab can, through parallel mechanisms, not only attenuate bone loss 6 , but also reduce body fat and improve energy homeostasis.…”
Section: Fsh Ab Reduces Adiposity In Ovariectomized Micesupporting
confidence: 48%
See 1 more Smart Citation
“…This clinical phenotype has often been documented in rodents post-ovariectomy, as well as in chronic hypoestrogenemic models, such as in female Erα −/− , aromatase −/− and Fshr −/− mice 4, 1618 , although in our hands, female Fshr −/− mice are not obese. While in female mice, genetic Fshr deficiency does not seem to protect against the pro-adiposity effects of severe chronic hypoestrogenemia, we questioned whether acute suppression of Fsh by an Fsh Ab can, through parallel mechanisms, not only attenuate bone loss 6 , but also reduce body fat and improve energy homeostasis.…”
Section: Fsh Ab Reduces Adiposity In Ovariectomized Micesupporting
confidence: 48%
“…There is also a sharp increase in visceral adiposity during this life stage, which coincides with the emergence of disrupted energy balance and reduced physical activity 3 . While the subsequent decline in estrogen explains menopausal bone loss in large part, effects of estrogen deprivation on visceral fat and whole body metabolism remain less clear 4 . We therefore questioned whether, by targeting FSH, we could not only prevent bone loss, but also reduce visceral adiposity and improve energy homeostasis.…”
mentioning
confidence: 99%
“…Ovariectomized animals present body weight gain and excessive feeding. The treatment of ovariectomized animals with estrogen prevents these changes, and these effects are mediated, in large part, through ERα (34,35). The present study demonstrated that the uterine weight of the rats that were administered YCJ at a dose equivalent to 75 ml/kg/day was not significantly different from that of the rats that were not administered YCJ.…”
Section: Weeks 12 Weeks ---------------------------------------------supporting
confidence: 50%
“…Of note is that the FSH antibodies, at the dosages used, do not affect serum estrogen levels (12,15), but this does not rule out equally relevant effects of estrogen on both bone mass and body fat (7,(24)(25)(26).…”
Section: Discussionmentioning
confidence: 99%
“…This reduced bone mass is also accompanied by increases in visceral adiposity, a disruption of energy metabolism, and decreased physical activity (5,6). These aberrations have been shown, in clinical studies, to be reversed by pharmacologic doses of estrogen (7).…”
Section: Introductionmentioning
confidence: 99%